The Role of Digitalization in Enhancing Public Service Effectiveness in Indonesia - Syamsiar Syamsiar (Jurnal Ilmiah Ilmu Administrasi Publik, 2023)
This qualitative research explores the role of digitalization in enhancing the effectiveness of public services in Indonesia. Against the backdrop of an increasingly digitalized world, the study aims to investigate the impact of digital initiatives on the efficiency and accessibility of public services in the Indonesian context. Employing a qualitative approach, data were collected through in-depth interviews with government officials, experts, and users of public services, allowing for a comprehensive understanding of the subject matter. The findings demonstrate that digitalization has played a significant role in improving the overall quality and responsiveness of public services in Indonesia. Furthermore, the study reveals key insights into the challenges and opportunities associated with implementing digital solutions in the public sector. The research contributes valuable knowledge to the ongoing discourse on leveraging digital technology to enhance public service delivery, thereby benefiting policymakers, practitioners, and citizens alike.